Institutional perceptions of opportunities and challenges of REDD+ in the Congo Basin - Brown, H.C.P.; Smith, B.; Sonwa, D.J.; Somorin, O.A.; Nkem, J. (2011)
Tropical forests have a central role to play in a new mechanism designed to mitigate climate change, known as REDD+ (Reduced Emissions From Deforestation and Forest Degradation). Through semistructured interviews and content analysis of relevant documents, the perceptions of the opportunities and challenges of REDD+ of institutions, who may be directly implicated in or affected by its implementation are investigated. Research takes place in three Central African countries, Cameroon, Central African Republic, and Democratic Republic of Congo, which contain the Congo Basin forest. Perception of opportunities include economic development and poverty reduction, biodiversity conservation, network building, and governance reform. Challenges identified include REDD+’s complexity, lack of technical capacity for implementation, opportunities for participation, benefit sharing, and the traditional system of shifting cultivation. Those involved in designing REDD+ internationally need to understand developing-country perspectives, and institutions at all levels need to work together to develop concrete strategies to improve overall outcomes.